Optimization Methods From Theory to Design Scientific and Technological Aspects in Mechanics - Cavazzuti, Marco; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book is about optimization techniques and is subdivided into two parts. In the first part a wide overview on optimization theory is presented. Optimization is presented as being composed of five topics, namely: design of experiment, response surface modeling, deterministic optimization, stochastic optimization, and robust engineering design. Each chapter, after presenting the main techniques for each part, draws application oriented conclusions including didactic examples. In the second part some applications are presented to guide the reader through the process of setting up a few optimization exercises, analyzing critically the choices which are made step by step, and showing how the different topics that constitute the optimization theory can be used jointly in an optimization process. The applications which are presented are mainly in the field of thermodynamics and fluid dynamics due to the author's background.
Part I Theory -- Design of experiments -- Response surface modelling -- Deterministic optimization -- Stochastic optimization -- Robust design analysis -- Part II Applications -- General guidelines: how to proceed in an optimization exercise -- A forced convection application: surface optimization for enhanced heat transfer -- A natural convection application: optimization of rib roughened chimneys -- An analytical application: optimization of a Stirling engine based on the Schmidt analysis and on the adiabatic analysis.
Keywords: Engineering design; Mathematical optimization; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Engineering Design; Optimization; Engineering Thermodynamics, Heat and Mass Transfer